(untitled) (Jurnal Penelitian Kehutanan Wallacea, 2023)
The Editorial Board has issued this editorial note in the form of a review to inform contributors about changes to the scope of the Journal of Wallacea Forestry Research (JPK Wallacea) following the transfer of management from Balai Penerapan Instrumen Lingkungan Hidup dan Kehutanan Makassar to Hasanuddin University’s Forest Conservation Study Program in 2023. JPK Wallacea is no longer limiting its scope to forestry and is expanded to cover biodiversity in general by incorporating the term Wallaceae, which is a biogeographical area located between the continents of Asia and Australia. This area is well known for its unique biodiversity both on land and in water. The Wallacea region’s biodiversity is famed for its distinctiveness yet, it is on the verge of extinction. Thus, the Editorial Board chose to focus on the scope of JPK Wallacea on scientific, technological, and policy conservation features. This scientific publication is expected to make a substantial contribution to the biodiversity conservation effort in the Wallacea region and its surroundings.